Uganda chicken genetic resources: I. phenotypic and production characteristics - Yussif, Illyass; Kugonza, Donald Rugira; Okot, Marion Wilfred; Amuge, Peace Oliver; Costa, Rosa; Dos Anjos, Filomena (Frontiers in Genetics, 2023)
The extent of diversity in the indigenous chicken breeds of Uganda was assessed for their potential utilisation in breeding programmes. A total of 293 indigenous-chicken-keeping households in villages across 35 districts forming 12 sub-regions of the four regions were randomly sampled for 586 mature chickens of both sexes. The study revealed that while only 20.8% of households were female-headed, 40.6% of indigenous chicken keepers were women. The production objectives were mainly focused on the chickens as sources of income from sales and household food. The chickens were predominantly managed in a scavenging (94.2%) feeding system in a mainly (96.9%) mixed crop-livestock system. The average flock size was 19.80±1.21 chickens with 3.83±0.29 laying hens, each producing an average of 13.41±0.20 eggs/clutch and 40.3±0.6 eggs/annum of 5.20±0.03-month egg production age. Normal feather strain predominated (>90%) with scattered incidences of naked-neck, frizzles, polydactyl and ptilopody in both sexes. Dark (49.0% hen; 43.8% cock) and white (38.3% hen; 42.4% cock) skin colours were most common among the chickens than those with yellow skin. However, yellow-coloured shanks were proportionally highest (41% cock; 29% hen). Orange and brown iris (eye) colours were the most common in both sexes. The hens commonly had small round earlobes with varying colours, while cocks had large oval-shaped, mainly red (70%) earlobes. The single comb type was dominant in both sexes, with wattles almost universally present. Frizzle and polydactyl allele frequencies were statistically lower (P<0.05) than the expected Mendelian proportions, indicating a possible state of endangerment. Meanwhile, the estimated allele frequencies of ptilopody, tufted-crest, and rose comb alleles in the population were similar (P>0.05) to the expected Mendelian frequencies. But these strains did not have any significant (P>0.05) influence on the body weight or all the linear morphometric estimates except for being marginally higher than the normal strains. Phenotypic correlations of body weight and morphometric traits ranged from 0.457 to 0.668 and 0.292 to 0.454 in cocks and hens, respectively. Hence, giving a hint about the prospects for improved performance with modifications in the production environment. The wide phenotypic diversity would therefore support management efforts for their sustainable utilisation and preservation.